THE RELATIONSHIP BETWEEN EARLY MARRIAGE AND THE INCIDENCE OF STUNTING - Wahida Wahida; Idayati Idayati; Ajeng Hayuning Tiyas; Gusriani Gusriani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Stunting is a chronic nutritional disorder influenced by multiple factors, including child marriage. West Sulawesi is one of the provinces in Indonesia with a high prevalence of both stunting and child marriage. This study aimed to examine the association between child marriage and stunting among children aged 23–59 months in Mamuju Regency. An analytical observational study with a cross-sectional design was conducted involving 62 mothers selected through purposive sampling. Data were collected through interviews and anthropometric measurements and analyzed using the chi-square test and Odds Ratio (OR). The results showed no significant association between child marriage and stunting (p = 0.667; OR = 0.72; 95% CI: 0.16–3.27). These findings suggest that stunting is a multifactorial condition influenced by various determinants beyond child marriage, highlighting the need for a comprehensive approach to its prevention. The Technology Readiness Level (TRL) of this study was Level 2.